Liquidity Management and Corporate Investment During a Financial Crisis - Campello, Murillo; Giambona, Erasmo; Graham, John R.; Harvey, Campbell R. (Review of Financial Studies, 2011)
[This article uses a unique dataset to study how firms managed liquidity during the 2008—2009 financial crisis. Our analysis provides new insights on interactions between internal liquidity, external funds, and real corporate decisions, such as investment and employment. We first describe how companies used credit lines during the crisis (access, size of facilities, and drawdown activity), the characteristics of these facilities (fees, markups, maturity, and collateral), and whether managers had difficulties in renewing or initiating lines. We also describe the dynamics of credit line violations and the outcome of subsequent renegotiations. We show how companies substitute between credit lines and internal liquidity (cash and profits) when facing a severe credit shortage. Looking at real-side decisions, we find that credit lines are associated with greater spending when companies are not cash-strapped. Firms with limited access to credit lines, in contrast, appear to choose between saving and investing during the crisis. Our evidence indicates that credit lines eased the impact of the financial crisis on corporate spending.]